Appropriate secondary prevention and clinical outcomes after acute myocardial infarction according to atherothrombotic risk stratification: The FAST-MI 2010 registry. (29th August 2020) - Tea, Victoria; Bonaca, Marc; Chamandi, Chekrallah; Iliou, Marie-Christine; Lhermusier, Thibaut; Aissaoui, Nadia; Cayla, Guillaume; Angoulvant, Denis; Ferrières, Jean; Schiele, François; Simon, Tabassome; Danchin, Nicolas; et al.
Abstract: Background: Full secondary prevention medication regimen is often under-prescribed after acute myocardial infarction. Design: The purpose of this study was to analyse the relationship between prescription of appropriate secondary prevention treatment at discharge and long-term clinical outcomes according to risk level defined by the Thrombolysis In Myocardial Infarction (TIMI) Risk Score for Secondary Prevention (TRS-2P) after acute myocardial infarction. Methods: We used data from the 2010 French Registry of Acute ST-Elevation or non-ST-elevation Myocardial Infarction (FAST-MI) registry, including 4169 consecutive acute myocardial infarction patients admitted to cardiac intensive care units in France. Level of risk was stratified in three groups using the TRS-2P score: group 1 (low-risk; TRS-2P=0/1); group 2 (intermediate-risk; TRS-2P=2); and group 3 (high-risk; TRS-2P≥3). Appropriate secondary prevention treatment was defined according to the latest guidelines (dual antiplatelet therapy and moderate/high dose statins for all; new-P2Y12 inhibitors, angiotensin-converting-enzyme inhibitor/angiotensin-receptor-blockers and beta-blockers as indicated). Results: Prevalence of groups 1, 2 and 3 was 46%, 25% and 29% respectively. Appropriate secondary prevention treatment at discharge was used in 39.5%, 37% and 28% of each group, respectively. After multivariate adjustment, evidence-based treatments at discharge were associated with lower rates of major adverse cardiovascular events (death, re-myocardial infarction or stroke) at five years especially in high-risk patients: hazard ratio = 0.82 (95% confidence interval: 0.59–1.12, p = 0.21) in group 1, 0.74 (0.54–1.01; p = 0.06) in group 2, and 0.64 (0.52–0.79, p < 0.001) in group 3. Conclusions: Use of appropriate secondary prevention treatment at discharge was inversely correlated with patient risk. The increased hazard related to lack of prescription of recommended medications was much larger in high-risk patients. Specific efforts should be directed at better prescription of recommended treatment, particularly in high-risk patients.